Level of exposure to fluorides by the consumption of different types of milk in residents from an area of Mexico with endemic hydrofluorosis - Liliana Valdez Jiménez; Jaqueline Calderón Hernández; Rosa Isela Córdova Atilano; Selene Yasmín Sandoval Aguilar; Jorge Alejandro Alegría Torres; Rogelio Costilla Salazar; Diana Rocha Amador (Elsevier, 2019)
Introduction: Several studies have shown the presence of fluorosis (DF) in primary dentition, suggesting an exposure to fluorides (F−) in early childhood. Breast milk is recommended as an exclusive food until 6 months of age. Although it is mentioned that only a small amount of F− can be eliminated by breast milk, studies have shown the presence of this element in milk of women living in contaminated areas, as well as in infant formulas. The objective of this project was to evaluate the exposure level to F− through milk in children living in an area with endemic hydrofluorosis. Methodology: The study included 110 children between 6 and 36 months of age from the municipality of Lagos de Moreno, Jalisco. Water samples were collected from the homes, as well as samples of milk (maternal, formula, whole or raw), and urine. Measurements were made with a selective ion electrode. The exposure level of F− for milk intake was calculated using the Oracle Crystal Ball package. Results: Levels greater than the reference level for DF were observed in infant formula reconstituted with public supply water, pasteurised cow's milk (whole) and untreated cow's milk treatment (raw) in the 90th, 70th, and 50th percentile, respectively, with a correlation being found between the levels of F− in milk and F− in urine (r = 0.41, P < 0.001). Conclusions: The identification of sources of F− in the early stages of child development could reduce the risk of developing DF. Resumen: Introducción: Diversos estudios han demostrado la presencia de fluorosis (FD) en la dentición primaria, lo que puede indicar una exposición a los fluoruros (F−) en la primera infancia. La leche materna se recomienda como alimento exclusivo hasta los 6 meses de edad. Aunque se menciona que solo una pequeña cantidad de F− puede eliminarse por leche materna, estudios han demostrado la presencia de este elemento en leche de mujeres residentes de zonas contaminadas, así como en leche de fórmulas comerciales. El objetivo del proyecto fue evaluar la dosis de exposición a F− a través de leche en niños residentes de una zona con hidrofluorosis endémica. Metodología: Un total de 110 niños de entre 6 y 36 meses de edad del municipio de Lagos de Moreno, Jalisco, México, participaron en el estudio. Se colectaron muestras de agua de los hogares, leche y orina. Las muestras se cuantificaron con el electrodo de ion selectivo. Se calculó la dosis de exposición a F− a través del programa Oracle Crystal Ball. Resultados: Se observaron dosis superiores a la dosis de referencia para FD en la leche de fórmula reconstituida con agua de abastecimiento público, de vaca pasteurizada (entera) y de vaca sin tratamiento sanitario (cruda) en el percentil 90, 70 y 50, respectivamente, así como una correlación entre los niveles de F− en leche y F− en orina (r = 0,41; p < 0,001). Conclusiones: La identificación de fuentes de F− en etapas tempranas del desarrollo infantil podría reducir el riesgo de presentar FD.